2004
DOI: 10.1128/jvi.78.20.11121-11129.2004
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Kaposi's Sarcoma-Associated Herpesvirus Latent Nuclear Antigen Leads to Abortive Episome Persistence

Abstract: Latent nuclear antigen (LNA) is implicated in Kaposi's sarcoma-associated herpesvirus (KSHV) episome persistence. LNA colocalizes with KSHV episomes on chromosomes in metaphase, and it maintains the stability and replication of KSHV terminal repeat-containing plasmids. In this study, we examined the function of LNA in episome persistence in the context of full-length KSHV genome by mutagenesis analysis. We generated a KSHV mutant, BAC36-⌬LNA, with LNA disrupted by transposon-based mutagenesis with a KSHV BAC c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
112
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(115 citation statements)
references
References 41 publications
3
112
0
Order By: Relevance
“…It has been shown that LANA autoactivates its own promoter; thus, the expression of LANA is maintained consistently at a high level by the regulation of this positive-feedback loop (33). High expression of LANA in KSHV-infected cells is one strategy for the virus to establish and maintain latent infection because down regulation of LANA expression results in disruption of viral latency (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that LANA autoactivates its own promoter; thus, the expression of LANA is maintained consistently at a high level by the regulation of this positive-feedback loop (33). High expression of LANA in KSHV-infected cells is one strategy for the virus to establish and maintain latent infection because down regulation of LANA expression results in disruption of viral latency (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…For example, bovine herpesvirus 4 (BoHV-4) encodes orthologues of ORF71 and ORF73, whereas ORF72 is absent (Zimmermann et al, 2001 pORF73 is the latency-associated nuclear antigen 1 (LANA-1) of HHV-8. LANA-1 associates with mitotic chromosomes to enable episome tethering during division of latently infected cells and its subsequent partitioning between daughter cells (Ballestas et al, 1999; Barbera et al, 2006;Ye et al, 2004). This crucial role in latency is reinforced by the ability of LANA-1 to modulate cellular pathways implicated in cell growth and survival by targeting transcriptional regulators or co-regulators such as p53, pRB, CBP and sin3A (Friborg et al, 1999;Krithivas et al, 2000;Lim et al, 2001;Radkov et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a recombinant bacterial artificial chromosome (BAC) containing the entire HHV-8 genome (HHV-8 BAC) was generated [30]. Using such technology, essential in vitro roles for RTA (ORF50) in viral reactivation, LANA (ORF73) in viral episome maintenance, and glycoprotein B (ORF8) for viral egress were clearly demonstrated, highlighting the usefulness of the HHV-8 BAC [14,27,28]. The lack of suitable animal models allowing the study of the tumorigenic potential of cells carrying WT HHV-8 prompted us to tackle this issue.…”
Section: Introductionmentioning
confidence: 99%